What Drives Firm Value in Emerging Markets? Evidence from Indonesian Telecom Firms - Pardomuan Sihombing; Aditya Sabrian Amirullah (SAN Scientific, 2026)
This study analyzes the effects of sustainability (ESG disclosure), business risk, dividend policy, and capital structure on firm value, with profitability as a mediating variable in telecommunications companies listed on the Indonesia Stock Exchange during 2020–2024. Although prior research has explored firm value determinants, findings on ESG disclosure and financial policies remain inconsistent, particularly in emerging markets, and few studies integrate these variables within a mediation framework. Using panel data analysis, the results indicate that ESG disclosure and dividend policy have a significant negative impact on firm value, suggesting that the market has not fully valued sustainability initiatives and views higher dividend payouts as limiting reinvestment opportunities. Conversely, capital structure and profitability show significant positive effects, emphasizing the importance of effective leverage management and strong earnings performance in influencing investor perceptions. Business risk has a positive but insignificant relationship with firm value. Mediation testing reveals that profitability mediates the relationship between capital structure and firm value, but does not mediate the effects of ESG disclosure, business risk, or dividend policy. These findings highlight the conditional role of profitability in linking financial decisions to firm value and suggest that ESG disclosure has not yet produced short-term valuation benefits in emerging markets.